c - THEA STILTON (New York: Scholastic Inc., 2015)
In Mice Take the Stage (Thea Stilton Mouseford Academy #7), the Thea Sisters compete for a chance to be the opening act for the famous Ratstreet Boys, who are performing at Mouseford Academy.
English